2020
DOI: 10.1002/jbio.201960154
|View full text |Cite
|
Sign up to set email alerts
|

Liver tissue classification of en face images by fractal dimension‐based support vector machine

Abstract: Full-field optical coherence tomography (FF-OCT) has been reported with its label-free subcellular imaging performance. To realize quantitive cancer detection, the support vector machine model of classifying normal and cancerous human liver tissue is proposed with en face tomographic images. Twenty samples (10 normal and 10 cancerous) were operated from humans and composed of 285 en face tomographic images. Six histogram features and one proposed fractal dimension parameter that reveal the refractive index inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Full-field optical coherence tomography (FF-OCT) has been recognized for its label-free subcellular imaging capabilities. Recently, Zhu et al [ 90 ] demonstrated the promise of their classifier using FF-OCT images for label-free, quantified tumor detection. This suggests that a fractal dimension-based classifier could potentially assist clinicians in identifying tumor boundaries for surgical resection in the future.…”
Section: The Fractal Nature Of the Gastrointestinal Systemmentioning
confidence: 99%
“…Full-field optical coherence tomography (FF-OCT) has been recognized for its label-free subcellular imaging capabilities. Recently, Zhu et al [ 90 ] demonstrated the promise of their classifier using FF-OCT images for label-free, quantified tumor detection. This suggests that a fractal dimension-based classifier could potentially assist clinicians in identifying tumor boundaries for surgical resection in the future.…”
Section: The Fractal Nature Of the Gastrointestinal Systemmentioning
confidence: 99%
“…(I-K) Boxplot of selected features for the Mean, Kurtosis, and FracDim. mean and kurtosis are not sensitive in distinguishing between normal and cancerous hepatocytes, the mean and kurtosis are not sensitive in distinguishing between normal and cancerous hepatocytes, when the liver becomes cancerous, the value of the fractal parameter increases ( 88 ). Copyright 2020, Wiley.…”
Section: Application Of Oct In Oncologymentioning
confidence: 99%
“…They used the label-free human liver tomography stack to extract seven quantitative parameters, including mean, variance, skewness, kurtosis, energy, entropy, and fractal dimension (FD). The value of FD grows as the liver becomes cancerous, signifying that a divided-dimensional classifier can be utilized for label-free quantitative tumor detection ( 88 ).…”
Section: Application Of Oct In Oncologymentioning
confidence: 99%
“…In a recent study, images from full-field optical coherence tomography were used to develop an SVM model that recognizes hepatic cancerous cells as a tool to detect tumor boundaries for resection intraoperatively[ 117 ]. A different study used X-ray imaging to develop a CNN model as the basis of a framework that automatically detects fiducial markers, performs 3D position reconstruction, and evaluates intrafraction motion during stereotactic body radiation therapy for liver malignancies[ 118 ].…”
Section: Applications Of Ai In Hcc Managementmentioning
confidence: 99%